Síntese, caracterização e atividade citotóxica de complexos de Pt(II), Pd(II) e Cu(II) contendo β-dicetonas - Almeida, Janaína do Couto (2014)
This work reports on the synthesis of four new Pt(II) and Pd(II) complexes of the type [M(O,O)(DMSO)Cl], where O,O = 4,4,4-trifluoro-1-phenyl-1,3-butanedione (HBTA) or 2-thenoyltrifluoroacetone (HTTA) and M = Pt(II) or Pd(II). It also describes the synthesis of Cu(II) complexes of the type [Cu(O,O)(N,N)X], where O,O = 4,4,4-trifluoro-1-phenyl-1,3-butanedione (HBTA), 1-(4-chlorophenyl)-4,4,4-trifluoro-1,3-butanedione (HBTACl) or 2-thenoyltrifluoroacetone (HTTA); N,N = 2,2-bipyridine (bipy) or 1,10-phenanthroline (phen) and X = NO3- or ClO4-. All complexes were characterized by elemental analysis, conductivity measurements, FT-IR, UV-Vis, high-resolution mass spectra (HRESIMS) and TG/DTA. The results indicate that the metallic ions bind to β-diketone via the oxygen atoms. For copper complexes, the molar conductivity values of 10−3 mol L-1 solutions of compounds in DMSO are in the range of 1:1 electrolytes. This indicates the labilization of the axial ligands in solution (the perchlorate or nitrate anion) resulting in the species [Cu(O,O)(N,N)]2+. The crystal structures of two compounds of copper(II) were determined by X-ray diffraction confirming the structural proposed for the copper complexes. All complexes were evaluated against chronic myelogenous leucemia cell line, K562 cells and IC50 values range from 2.1-51.9 μmol L-1. The results showed that six complexes are more cytotoxic than the carboplatin. As example, the compound [Cu(BTACl)(phen)NO3] is approximately five times more active that the carboplatin (IC50 = 10.0 μmol L-1).